KEDUDUKAN KEPEMILIKAN ATAS TANAH TERHADAP SERTIFIKAT TANAH YANG DI LELANG DI BANK DANAMON KABUPATEN GORONTALO - ALINTI, SITI NURHALIZAH; JUNUS, NIRWAN; MANDJO, JULIUS T.; KADIR, MUHAMAD KHAIRUN KURNIAWAN; ELFIKRI, NURUL FAZRI; MAMU, KARLIN Z. (Universitas Mahasaraswati K. Mataram, 2024)
The purpose of this study is to ascertain the status of property ownership rights with reference to land certificates that Bank Danamon has put up for auction. In addition, the purpose of this study is to determine the degree of legal protection afforded to the owners of land rights that Bank Danamon has auctioned off. Using a statutory method, a comparison approach, and a case approach, the researcher employed a normative-empirical style of legal research to compile this study. The findings of this study demonstrate that the Bank disregarded the verbal agreement between the debtor and creditor and held the auction without a third summons, in violation of the auction regulations